2018
DOI: 10.1002/bies.201700245
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Metabolic Control of Lymphangiogenesis

Abstract: Lymphangiogenesis is an important developmental process that is critical to regulation of fluid homeostasis, immune surveillance and response as well as pathogenesis of a number of diseases, among them cancer, inflammation, and heart failure. Specification, formation, and maturation of lymphatic blood vessels involves an interplay between a series of events orchestrated by various transcription factors that determine expression of key genes involved in lymphangiogenesis. These are traditionally thought to be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Some studies have indicated the presence of lymphatic vessels in tumors, while others have demonstrated contrasting results ( 10 , 39 ). Although it remains controversial whether tumors can induce the genesis of lymphatic vessels, it has been demonstrated that the excessive expression of lymphogenerative factors, such as VEGF-C, can induce more lymphatic vessels and facilitate metastasis through tumor lymphatic vessels ( 14 ). In experiments using mouse tumor models, it has been demonstrated that VEGF-C induces lymphangiogenesis and that tumor cells enter the capillary lymphatic vessels ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated the presence of lymphatic vessels in tumors, while others have demonstrated contrasting results ( 10 , 39 ). Although it remains controversial whether tumors can induce the genesis of lymphatic vessels, it has been demonstrated that the excessive expression of lymphogenerative factors, such as VEGF-C, can induce more lymphatic vessels and facilitate metastasis through tumor lymphatic vessels ( 14 ). In experiments using mouse tumor models, it has been demonstrated that VEGF-C induces lymphangiogenesis and that tumor cells enter the capillary lymphatic vessels ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiogenesis is a complex process regulated by a number of factors ( 14 ). It has been reported that vascular endothelial growth factor-C (VEGF-C) and its receptor, VEGFR-3, are the basis of lymphatic vessel formation ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite lesser ATP generation compared with oxidative phosphorylation, the up-regulated glycolysis meets the metabolic requirements of cell proliferation by affording adequate energy and sufficient glycolytic intermediates for macromolecular synthesis (eg, amino acids, phospholipids, and nucleic acids). 2,3 Moreover, the findings from a previous study 4 showed that the glycolysis level in endothelial cells (ECs) was much higher than that in other noncancer type of cells and largely comparable to that in tumor cells. EC metabolism has recently emerged as an important regulator of angiogenesis and lymphangiogenesis.…”
mentioning
confidence: 94%
“…Recent advances have identified endothelial cell metabolism as a novel regulator of lymphatic vessel formation [17][18][19][20]. We and others found that glycolysis, which refers to a series of biochemical processes that convert glucose to pyruvate, provides more than 70% of ATP in LECs [21,16].…”
Section: Introductionmentioning
confidence: 99%